2018
DOI: 10.1590/2179-8087.039116
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils for Alternative Teak Rust Control

Abstract: The objectives of this study were to evaluate the effect of lemon grass, citronella grass, Mexican-tea and noni essential oils on urediniospore germination of Olivea neotectonae, the agent responsible for rust in Teak (Tectona grandis L.f.); to evaluate the phytotoxic effect of these essential oils on teak seedlings; and to evaluate the use of essential oils to control rust in teak plants when preventively and curatively applied. We found that the noni and lemon grass essential oils inhibited 100% of uredinios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
(18 reference statements)
1
11
0
4
Order By: Relevance
“…From chromatographic analyses, the main components of noni and rosemary pepper oils identified were octanoic acid and thymol, respectively. These components are possibly responsible for the antifungal action of these oils [14,22,23]. Other studies validate the data obtained in This study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…From chromatographic analyses, the main components of noni and rosemary pepper oils identified were octanoic acid and thymol, respectively. These components are possibly responsible for the antifungal action of these oils [14,22,23]. Other studies validate the data obtained in This study.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies validate the data obtained in This study. Octanoic acid is the component at the highest concentration in the oil of M. citrifolia [23][24][25], and thymol is a major component of the oil of Lippia sidoides [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…Veras et al (2014) and Fontenelle et al (2007) reported the presence of 84.9 and 59.65% of thymol, respectively, as a major constituent in essential oils of L. sidoides. Different values were reported by Osorio et al (2018), where they obtained 64.03% concentration of octanoic acid (caprylic acid) and 8.64% hexanoic acid (caproic acid) in M. citrifolia essential oil. Pino et al (2010) identified 96 compounds, of which octanoic acid (70%) and hexanoic acid (8%) were the major components.…”
Section: Chemical Constituents Of Lippia and Noni Essential Oilsmentioning
confidence: 83%
“…Dessa forma, houve o controle parcial da doença, atrasando a evolução da mesma. Osorio et al (2018) comprovaram que o controle da ferrugem na Teca obtido pela aplicação do óleo essencial, de noni foi parcial, possivelmente devido à presença de compostos tóxicos em grande quantidade nos óleos essenciais.…”
Section: Teste In Vivounclassified
“…O óleo de noni obteve melhor eficiência no controle preventivo quando comparado ao curativo. Estes resultados são semelhantes aos encontrados por Osorio et al (2018) que apontam resultados semelhantes para o óleo de noni. Sahoo et al (2012) observaram potencial fungitóxico do extrato de folhas de noni sobre as espécies fúngicas Aspergillus niger, Aspergillus fumigatus, Rhizopus oryzae, Helminthosporium sp.…”
Section: Teste In Vivounclassified